Study on The Performance of a Tubular Enzyme Reactor - T Utami (Indonesian Food and Nutrition Progress, 1994)
The residence time distribution of fluid passing through a tubular reactor was studied to predict the performance of a tubular enzyme reactor. It was found that there was a great amount of dispersion from the ideal plug-flow over the range of flow rate of 15 ml/min to 78 ml/min. Sucrose hydrolysis by yeast invertase has been selected as an enzymatic model reaction in a tubular reactor. The kinetics of invertase were studied by the observation of the initial rates of reaction at various substrate concentrations.            A mathematical model which described the degree of conversion of a tubular enzyme reactor as a function of flow rate is developed. The expression of the rate of reaction is approximated by a linear function using Maclaurin theorem. The dispersion model shows good agreement with the observations on sucrose hidrolyzed by invertase in a tubular reactor.